Combined Liquid and Solid-Phase Extraction Improves Quantification of Brain Estrogen Content - Chao, Andrew; Schlinger, Barney A.; Remage-Healey, Luke (Frontiers in Neuroanatomy, 2011)
Accuracy in quantifying brain-derived steroid hormones (‘neurosteroids’) has become increasingly important for understanding the modulation of neuronal activity, development, and physiology. Relative to other neuroactive compounds and classical neurotransmitters, steroids pose particular challenges with regard to isolation and analysis, owing to their lipid solubility. Consequently, anatomical studies of the distribution of neurosteroids have relied primarily on the expression of neurosteroid synthesis enzymes. To evaluate the distribution of synthesis enzymes vis-à-vis the actual steroids themselves, traditional steroid quantification assays, including radioimmunoassays (RIA), have successfully employed liquid extraction methods (e.g., ether, dichloromethane or methanol) to isolate steroids from microdissected brain tissue. Due to their sensitivity, safety and reliability, the use of commercial enzyme immunoassays (EIA) for laboratory quantification of steroids in plasma and brain has become increasingly widespread. However, EIAs rely on enzymatic reactions in vitro, making them sensitive to interfering substances in brain tissue and thus producing unreliable results. Here, we evaluate the effectiveness of a protocol for combined, two-stage liquid/solid phase extraction as compared to conventional liquid extraction alone for the isolation of estradiol (E2) from brain tissue. We employ the songbird model system, in which brain steroid production is pronounced and linked to neural mechanisms of learning and plasticity. This study outlines a combined liquid-solid phase extraction protocol that improves the performance of a commercial EIA for the quantification of brain E2 content. We demonstrate the effectiveness of our optimized method for evaluating the region specificity of brain E2 content, compare these results to established anatomy of the estrogen synthesis enzyme and estrogen receptor, and discuss the nature of potential EIA interfering substances.